Evaluation of Ejection Fraction in Patients with cardiac Resynchronization Therapy by Two and Three Dimensional Echocardiography - OM, Anil (Journal of Institute of Medicine Nepal, 2014)
Introduction: Since assessment of left ventricular ejection fraction (LVEF) is crucial for evaluation of patients with cardiac resynchronization therapy (CRT) device both for selection of potential candidates for CRT as well as assessing outcome of therapy, we compared LVEF in patients with CRT device by two dimensional and three dimensional echocardiography. Methods: Two dimensional echocardiography (2DE) was performed first with CRT device on. LVEF obtained by modified biplane Simpson’s Rule. Then real time three dimensional echocardiography (3DE) was performed by (iE 33, PHILIPS Machine). Procedure was repeated with CRT device off. Results: A total of 19 patients aged 54.6 ±11.2 years (Range: 32 years to 75 years) were studied. LVEF measured by 2DE and 3DE, with CRT device off, was 22±4% (17-27%) and 24 ±3% (15-27%) respectively. With CRT device on, LVEF measured by 2DE and 3DE was 26.6±4.1% (22-32%) and 31.3±5.8% (25-41%) respectively. Conclusion: Two dimensional echocardiography underestimates LVEF as compared to three dimensional echocardiography. Cardiac resynchronization therapy (CRT) improves LVEF measured either by two or three dimensional echocardiography.